EFL Students’ Experiences with Pronunciation Problems in Speaking Performance - Maysabella; Nazlin Nazlin; Fella Marwanda; Reyza Uswatun Hasanah (Media Akademika Publisher, 2026)
This study aims to examine the fourth-semester students' pronunciation issues of the English Language Education Study Program at Universitas Islam Indragiri. Adopting a descriptive method supported by qualitative data, the study collected data from twenty-one students through questionnaires and interviews. It examined five indicators of perception: the difficulty of pronouncing specific sounds, anxiety caused by pronunciation errors, decreased speaking fluency, lack of knowledge about pronunciation, and the impact of incorrect pronunciation on listener comprehension. The findings reveal that many students have pronunciation issues that impede their confidence, speaking fluency, and overall effectiveness in communication. Although formal instruction in pronunciation is still not wide-ranging, the students are strongly motivated to work on their own through practice and technology use. The study calls for a more systematic and supportive model of pronunciation teaching in the English language curriculum.